EXPERIMENTAL AND NUMERICAL EVALUATION OF AN IN-FLIGHT ANGLE OF ATTACK MEASUREMENT SYSTEM FOR HIGH POWER MODEL ROCKETS - Fernandes, C. D.; Coutinho, B. H.; Borges, B. F.; Iwamoto, B. H.; Silva, D. Z. C.; Fontoura, I. S.; Braun, L. P. B.; Lüdtke, W. R.; Junior, A. A. M. O. (Revista de Engenharia Térmica, 2023)
The angle of attack (α) affects the drag, flight path, and flight stability during rocket ascent. This work proposes an in-flight α measurement system based on pressure measurements at the surface of the nosecone for low apogee rockets. An electronic micro differential pressure transducer was selected to measure the pressure difference between selected points in the rocket’s nosecone. Wind tunnel tests were performed to correlate the α with the sensor output at low Mach numbers (Ma ≃ 0.08). The experimental results were further used as a reference for the construction of CFD models of the external flow in the rocket’s nosecone with the aim of predicting the measurements in an extended Mach number range (up to Ma ≃ 0.7). The numerical results allowed for an extended model correlating α with the differential pressure transducer output (Ch). The estimate of model’s errors completes the analysis.